2018
DOI: 10.1016/j.anireprosci.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of testicular biometry with semen variables in breeding soundness evaluation of Nellore bulls

Abstract: This study aimed to evaluate the correlation between testicular biometry and semen variables, as well as, to relate testicular variables to the probability of selecting Nellore bulls with desirable sperm morphology when conducting breeding soundness evaluations (BSE). A total of 2055 BSEs from 506 bulls comprised the dataset. Biometric variables evaluated were: scrotal circumference, testicular volume, width, length, ratio and eccentricity; and semen variables were sperm motility, major sperm defects, minor sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Scrotal circumference is a predictor of fertility in bulls` daughters [ 27 , 28 ]. A study based on 2,055 Nellore bulls at five different ages reported average SC ranging from 32.10 cm to 40.00 cm in animals from 18 to 48 months or more [ 29 ]. Usually, taurine ( Bos taurus taurus ) bulls with ages around 12 to 15 months present SC values of 30 cm on average at the beginning of the breeding season.…”
Section: Discussionmentioning
confidence: 99%
“…Scrotal circumference is a predictor of fertility in bulls` daughters [ 27 , 28 ]. A study based on 2,055 Nellore bulls at five different ages reported average SC ranging from 32.10 cm to 40.00 cm in animals from 18 to 48 months or more [ 29 ]. Usually, taurine ( Bos taurus taurus ) bulls with ages around 12 to 15 months present SC values of 30 cm on average at the beginning of the breeding season.…”
Section: Discussionmentioning
confidence: 99%
“…The breeding soundness evaluation (BSE) is very useful to select bulls in breeding programmes; the evaluation of SC for many years has been used and contributed to this selection. However, the inclusion of measurement of testicular parameters and the testicular volume could bring a more accurate evaluation because there is a positive correlation with semen variables (Penitente Filho et al., 2018) and may yield superior results, including Bos taurus indicus crossbred bulls (Vijetha et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These factors can also be influenced by the environment, nutrition, age, breed, and genetics (Menegassi et al, 2015). The SC is the most commonly used and perhaps the most important reproductive trait in young bulls; it has strong and favourable correlations with several reproductive traits measured in both the bull (semen quality) and their female progeny (age at puberty, age at first calving, probability of pregnancy at 14 months, pregnancy rate, and ovulation rate) (Burns et al, 2011; Penitente‐Filho et al, 2018; Santana Jr et al, 2012). Although these factors have been reported and investigated, the effect of the calving date on the sperm quality and BSE result of future sires remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%